I'll be you : a novel - Brown, Janelle (Random House, 2022)
"As children, Sam and Elli were two halves of a perfect whole: Gorgeous identical twins whose parents sometimes couldn't even tell them apart. They fell asleep to the sound of each other's breath at night, holding hands in the dark. And once Hollywood discovered them, they became B-list child TV stars, often inhabiting the same role. But as adults their lives have splintered. After leaving acting, Elli reinvented herself as the perfect suburban wife: Married to a real-estate lawyer, in a house two blocks from the beach. Meanwhile, Sam has never recovered from her failed Hollywood career, or from her addiction to the pills and booze that have propped her up for the last fifteen years. After her destructive behavior finally drove a wedge between them, Sam hasn't spoken to her sister in a year when their father calls out of the blue. Unbeknownst to Sam, Elli's life lately has been in turmoil: Her husband moved out, and Elli just adopted a two-year-old girl. Now she's checked in to a mysterious spa in Ojai, and has stopped answering her phone. As Sam works to connect the dots left by Elli's baffling disappearance, she realizes that the bond between her and her sister is more complicated than she ever knew"--